Safety and efficacy of propofol anesthesia for pediatric target-controlled infusion in children below 3 years of age: a retrospective observational study. Issue 10 (3rd October 2018) - Kang, Pyoyoon; Jang, Young-Eun; Kim, Eun-Hee; Lee, Ji-Hyun; Kim, Jin-Tae; Kim, Hee-Soo
ABSTRACT: Background : Although the requirement of propofol in children is increasing, propofol for induction and maintenance of anesthesia below 3 years old has not been approved in Korea. This study can provide a clinical evidence to increase the range of approval. Research design and methods : We reviewed the medical records of patients below 3 years of age who underwent surgery between September 2013 and December 2016. Safety was evaluated on the basis of vital signs, and laboratory findings and efficacy were evaluated on the basis of the bispectral index (BIS). Adverse events were examined. Results : A total of 109 patients anesthetized with propofol (propofol group) were compared with 109 patients with volatile anesthetics (volatile group) after propensity score matching. There was a difference in the proportion of patients showing decreased systolic pressure ( P < 0.001) and heart rate ( P = 0.03), but there was no difference in diastolic pressure ( P = 0.238), mean arterial pressure ( P = 0.175) during surgery. After surgery, there was no difference in all vital signs and the proportion patients who experienced adverse events of two groups. Conclusions : Propofol anesthesia by target-controlled infusion was effective and didn't show serious propofol-related perioperative adverse events.